OFDM techniques for wireless communications - Zheng, Wendy Wenlin. (2009)
The purpose of this report is to study the characteristic and performance of Orthogonal Frequency Division Multiplexing (OFDM) system This report investigates the performance of OFDM. OFDM is becoming more and more popular and is the preferred modulation technique for wireless communications as compare to other modulation techniques. The reason why OFDM is the chosen modulation is because it can provide large data rates with sufficient robustness to radio channel impairments. Some advantages of using OFDM includes high spectral efficiency, its robustness to the channel fading, its immunity to impulse interference and its ability in handling very strong echoes. Therefore the aim of this report is to study and investigate how some factors like noise and multi-path fading affect the performance of OFDM. The report will determine the performance based on the various graphs with the bit error rate (BER) against the Signal to Noise Ratio (SNR) value. The performance of OFDM was accessed by using computer simulations performed using Matlab.